Lipase spesifik 1,3-gliserida dari fungi lokal untuk biokonversi CPO menjadi diasilgliserol Specific lipase of 1,3-glyceride from indigenous fungi for bioconversion of CPO to produce diacylglycerol - . TRI-PANJI; . SUHARYANTO; Nining ARINI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2008)
SummaryDownstream industry of palm oil producing specialty oil with higher economic value compared to that of CPO in Indonesia is less developed due to technical obstacle and the availability of supporting materials. Specific lipase 1,3-glyceride for example which is used for oleochemical processing of healthy oil production is still imported with relatively high price. Healthy oil can be made from CPO bioconversion using the enzyme that produces oil rich in diacylglycerol (DAG). Although research on the production and the use of lipase has been well studied, production of specific lipase from microbes of local source is still very limited. This article reports one part of the series of the research activities on bioprocess and genetic engineering approaches to produce specific lipase for bioconversion of CPO i.e optimization of 1,3-glyceride-spesific lipase production from fungi selected from local sources. Based on the fluorescence zone on the screening media, of the twenty isolates collection, it was found that P6 isolate, thereafter indentified as Neurospora sitophila, has the highest activity of 1,3-glyceride-specific lipase. The lipase of N. sitophila was able to catalyze glycerolysis of triacylglycerol (TAG) in CPO to produce DAG. The bioconversion products of lipase yielding ratio of DAG/TAG was higher than ratio of free fatty acids (FFA)/TAG (0.12 > 0.08). The optimum condition of the enzymatic bioconversion was at 40 oC, pH 6, and 10-day incubation. The primary fatty acids on the DAG were oleic (56.2%), palmitic (40.0%), and myristic (2.7%) acids. The decrease of palmitic acid on DAG compared to on TAG, indicated that the lipase of N. sitophila worked relatively specific at C1 or C3 of the TAG.Kurang berkembangnya industri hilir yang menghasilkan minyak khusus yang nilainya berlipat dibandingkan CPO antara lain karena hambatan teknis dan ketersediaan bahan pendukungnya. Lipase spesifik 1,3-gliserida misalnya, yang digunakan untuk produksi minyak kesehatan, masih diimpor dengan harga relatif tinggi. Minyak kesehatan dapat diproduksi dari biokonversi CPO dengan lipase spesifik 1,3-gliserida hingga diperoleh minyak yang kaya kandungan diasilgliserol (DAG). Tulisan ini melaporkan optimasi aktivitas lipase spesifik 1,3-gliserida dari fungi isolat lokal terpilih. Berdasarkan zona fluoresens pada medium penapis lipase, dari 20 isolat fungi yang diuji isolat P6 yang kemudian diidentifikasi sebagai Neurospora sitophila memiliki aktivitas tertinggi dan bersifat spesifik 1,3-gliserida. Lipase N. sitophilamampu mengkatalisis gliserolisis triasilgliserol (TAG) dalam CPO untuk menghasilkan DAG. Lipase tersebut menghasilkan nilai perban-dingan DAG/TAG lebih besar dari nilai perbandingan asam lemak bebas (ALB)/TAG (0,12 > 0,08). Kondisi optimum biokonversi enzimatis ini terjadi pada suhu 40 oC, pH 6, dan waktu inkubasi selama 10 hari. Asam lemak utama penyusun DAG adalah asam oleat (56,2%), palmitat (40,0%), dan miristat (2,7%). Berkurangnya asam palmitat pada DAG dibanding pada TAG menunjukkan bahwa lipase N. sitophila bekerja secara relatif spesifik pada C1 atau C3 dari gliserida.